2008
DOI: 10.1002/adsc.200800239
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Brønsted Acid‐Mediated Enantioselective Organocatalytic Three‐Component Reaction for the Construction of Trifluoromethyl‐Containing Molecules

Abstract: In combination with the advantages of organocatalysis, we have developed a highly enantioselective Friedel-Crafts aminoalkylation of indoles with imines generated in situ from trifluoroacetaldehyde methyl hemiacetal and aniline. Novel chiral trifluoromethyl-containing compounds were obtained in high yields with excellent enantioselectivities. This methodology was further extended to difluoroacetaldehyde methyl hemiacetal to demonstrate the broad scope of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 65 publications
0
48
0
1
Order By: Relevance
“…Ma and co-workers reported an enantioselective Friedel-Crafts reaction of indoles with imines generated in situ from trifluoroacetaldehyde or difluoroacetaldehyde methyl hemiacetal and aniline by utilizing chiral catalyst 116e. High yields (80-99%) and excellent enantioselectivities (79-98% ee) have been obtained for a wide scope of indoles [105].…”
Section: Phosphoric Acid and Amide Catalysismentioning
confidence: 98%
“…Ma and co-workers reported an enantioselective Friedel-Crafts reaction of indoles with imines generated in situ from trifluoroacetaldehyde or difluoroacetaldehyde methyl hemiacetal and aniline by utilizing chiral catalyst 116e. High yields (80-99%) and excellent enantioselectivities (79-98% ee) have been obtained for a wide scope of indoles [105].…”
Section: Phosphoric Acid and Amide Catalysismentioning
confidence: 98%
“…[10] Recently, we have demonstrated that chiral phosphoric acids can catalyze some arylation reactions of trifluoroacetaldimines (generated in situ) and simple trifluoromethyl ketones with good to excellent enantioselectivities. [11] As a part of our ongoing studies, we would like to report our preliminary results on chiral Brønsted-acid-catalyzed enantioselective direct arylation of ethyl 4,4,4-trifluoroacetoacetate (ETFAA) and ethyl trifluoropyruvate.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In this regard, our group has developed a highly enantioselective F-C aminoalkylation of indoles with aldimines generated in situ from trifluoro-A C H T U N G T R E N N U N G acetaldehyde methyl hemiacetal and aniline (Scheme 1a). [4] Bolm and co-workers described an organocatalyzed F-C reaction of indoles with trifluoropyruvate-derived imines to afford trifluoromethylamines with a tetrasubstituted carbon stereocenter (Scheme 1b). [5] However, the electrophilic partners were limited to acyclic imines.…”
mentioning
confidence: 98%
“…The TLC detection showed that the reaction was complete after 12 h. The desired product 4a was achieved in 96% yield, but only a moderate ee value (36%) was observed ( Table 1, entry 1). To improve the enantioselectivity, chiral phosphoric acids with various substitutents at the 3,3'-positions of the BINOL scaffold were evaluated, and the 2,4,6-triisopropylphenyl-substituted catalyst 1f was found to be the best (97% yield, 78% ee) ( Table 1, entries [1][2][3][4][5][6]. A survey of solvents indicated that CH 2 ClCH 2 Cl (DCE) was optimal in terms of yield and enantioselectivity (Table 1, entries 7-11).…”
mentioning
confidence: 99%